Correspondence of Florence O'Donoghue with various individuals (J - K) attempting to gather evidence regarding events in Cork up to and including Easter Week 1916 - O'Donoghue, Florence, 1895-1967 (1947)
Correspondents are William Jones, R.P. Keyes, Joe Kenny and William Kent.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Irish Republican Army; Bureau of Military History, 1913-1921; Ireland -- History -- 1922-; Ireland -- History -- Easter Rising, 1916